Interleukin-8 expression differences in chronic and active chronic inflammation gastric mucosa biopsy with helicobacter pylori infection - Muhammad Arif; Siti Nurdjanah; Neneng Ratnasari (Acta Interna The Journal of Internal Medicine, 2017)
Background: Infection with Helicobacter pylori (HP) estimated to occur in 50% of the population in the world. Helicobacter pylori infection causes inflammation of the gastric mucosa and gastric epithelial release of interleukin-1β, interleukin-6, interleukin-8 and tumor necrosis factor α. Interleukin-8 plays a role in the degree of chronic inflammation of the gastric mucosa and gastric cancer risk. There has been no research on differences in the expression of interleukin-8 is based on chronic and chronic active inflammation on biopsy of the gastric mucosa with Helicobacter pylori infection in Hospital Dr. Sardjito.Objective: To prove the differences in the expression of interleukin-8 of chronic inflammation and gastric mucosal biopsy active chronic infection with Helicobacter pylori.Methods: This study used a cross-sectional design. Examined the expression of interleukin-8 on the rest of the biopsy sample HP (+) in August 2009 to March 2014. Classification of chronic inflammatory and chronic active obtained through histopathology report. Categorical numerical data from the two groups, unpaired, the distribution is not normal: Mann-Whitney test. Differences were considered significant if it was obtained p <0.05 with a confidence interval of 95%.Results: There were 41 samples of gastric mucosa biopsy preparations, comprising 9 samples of chronic inflammation and 32 samples of chronic inflammatory active of the gastric mucosa. The median value of the expression of IL-8 eptitel surface on chronic inflammation by 83 (40-94)% and the active chronic inflammation by 82 (19-94). Comparison test with Mann Whitney U test. From the statistical calculations p value = 0.887  with p> 0.05Conclusion: There is no difference in the expression of interleukin-8 in inflammatory chronic active and chronic inflammation of the gastric mucosa with Helicobacter pylori infection.Keywords: Helicobacter pylori, interleukin-8, chronic inflammation and chronic inflammatory active.